G6PD A- is the major cause of G6PD deficiency among the Siddis of Karnataka, India - Rati Devendra; Vinod Gupta; Somashekhar S. Biradar; Pradeep Bhat; Shantharam Hegde; S. L. Hoti; Malay B. Mukherjee; Harsha V. Hegde (Taylor & Francis Group, 2020)
Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common human erythroenzymopathy affecting more than 400 million people worldwide. G6PD deficiency was reported in India more than 50 years ago and the prevalence rate varies from 5.7% to 27.9% in different caste and tribal groups. Aim: To study the prevalence of, and the mutations causing, G6PD deficiency among the Siddis of Karnataka. Subjects and methods: A total of 755 individuals were screened using the DPIP dye decolorisation method and the deficiency was further confirmed by quantitative assay. Molecular characterisation was performed by PCR-RFLP method and DNA sequencing. Biochemical characterisation was performed as per WHO criteria. Results: Of the 755 individuals, 71 individuals (9.4%) were found to be G6PD deficient with an enzyme activity ranging from 0.02 to 3.83 IU/gm Hb. Mutational analysis could be performed on 49 G6PD deficient individuals and 45 (91.8%) of them showed the presence of the G6PD A- variant while the remaining 4 (8.2%) had the G6PD Kerala-Kalyan mutation. Microsatellite analysis in G6PD A- individuals showed the presence of 166/195 bp, AC/CTT alleles. Conclusions: G6PD deficiencies among the Siddis are predominantly due to G6PD A- mutation. Furthermore, biochemical parameters and the microsatellite repeat markers in the Siddi A- chromosome confirmed they are African descendants with Indian admixture.